The number of mice in the field after 1 year is 221 mice.
Given data:
If the population of mice in the field grows exponentially, we can use the exponential growth formula to determine the future population.
The exponential growth formula is given by:
P(t) = P₀ * e^(kt)
Where:
P(t) is the population at time t,
P₀ is the initial population,
e is Euler's number (approximately 2.71828), and
k is the growth rate.
So, the initial population (P₀) is 3 mice, and after five months, the population (P(t)) is 18 mice.
18 = 3 * e^(5k)
Dividing both sides by 3, we get:
6 = e^(5k)
To solve for k, we can take the natural logarithm (ln) of both sides:
ln(6) = 5k
k = ln(6) / 5 ≈ 0.35835
So, the growth rate is k = 0.3583
Now that we have the growth rate, determine the population after 1 year (12 months).
Substituting the values into the formula:
P(12) = 3 * e^(0.35835 * 12)
Calculating this expression, we find:
P(12) ≈ 3 * e^(4.3) ≈ 3 * 73.699 ≈ 221.09
Hence, it is expected that there will be approximately 221 mice in the field after 1 year if the population grows exponentially.
To learn more about exponential growth factor click :
https://brainly.com/question/13674608
#SPJ2
Final Answer:
After 1 year, the field is expected to have approximately 221 mice.
Explanation:
To solve this exponential growth problem, we'll use the exponential growth formula:
[tex]\[ P(t) = P_0 \times e^{rt} \][/tex]
where:
- [tex]\( P(t) \)[/tex] is the population at time t,
- [tex]\( P_0 \)[/tex] is the initial population size,
- r is the growth rate,
- e is Euler's number (approximately 2.71828),
- t is the time in consistent units.
We need to find the growth rate r using the information that we have (the initial population [tex]\( P_0 \)[/tex] is 3, and after 5 months,[tex]\( P(5) \)[/tex] is 18). Then, we'll calculate the population after 1 year (12 months).
Let's apply the given values to the formula at t = 5 months:
[tex]\[ 18 = 3 \times e^{5r} \][/tex]
Now we need to solve for r. We start by dividing both sides of the equation by 3:
[tex]\[ 6 = e^{5r} \][/tex]
Next, we take the natural logarithm (ln) of both sides to solve for r. The natural logarithm of [tex]\( e^{5r} \)[/tex] is equal to 5r:
[tex]\[ \ln(6) = 5r \][/tex]
Now we divide by 5:
[tex]\[ \frac{\ln(6)}{5} = r \][/tex]
We can use a calculator to find r. The natural logarithm of 6 is approximately 1.79176, so:
[tex]\[ r = \frac{1.79176}{5} \\\\\[ r \approx 0.358352 \][/tex]
Now that we have the monthly growth rate r, we can use it to find the population after 12 months. Plugging r, [tex]\( P_0 \)[/tex], and t = 12 months into the exponential growth formula, we get:
[tex]\[ P(12) = 3 \times e^{0.358352 \times 12} \][/tex]
Using a calculator, we compute the value of [tex]\( e^{0.358352 \times 12} \)[/tex], which is approximately [tex]\( e^{4.300224} \)[/tex].
[tex]\[ P(12) = 3 \times e^{4.300224} \][/tex]
Using a calculator to find [tex]\( e^{4.300224} \)[/tex], we get a value of approximately 73.699.
[tex]\[ P(12) = 3 \times 73.699 \\\\\[ P(12) \approx 221.097 \][/tex]
Since we can't have a fraction of a mouse, we would round to the nearest whole number.
Thus, after 1 year, the field is expected to have approximately 221 mice.
finding whole number equal to fraction 8/1
Answer: 8
Step-by-step explanation: 8 divided by 1 is 8
8 is the whole number equal to fraction 8/1.
What is Number system?A number system is defined as a system of writing to express numbers.
The given fraction is 8/1
Eight divided by one.
A fraction represents a part of a whole or, more generally, any number of equal parts.
8 is the numerator and 1 is the denominator.
The complete set of natural numbers along with '0' are called whole numbers.
If a number is divided by another number then the result will be the numerator which is whole number.
8/1=8
Hence, 8 is the whole number equal to fraction 8/1.
To learn more on Number system click:
https://brainly.com/question/22046046
#SPJ2
please Answer fast .......
Answer:
Option 3 [tex]\frac{67}{441}[/tex]
Step-by-step explanation:
step 1
Find the roots of the quadratic equation
we have
[tex]3x^{2}+5x-7=0[/tex]
The formula to solve a quadratic equation of the form [tex]ax^{2} +bx+c=0[/tex] is equal to
[tex]x=\frac{-b(+/-)\sqrt{b^{2}-4ac}} {2a}[/tex]
in this problem we have
[tex]3x^{2}+5x-7=0[/tex]
so
[tex]a=3\\b=5\\c=-7[/tex]
substitute in the formula
[tex]x=\frac{-5(+/-)\sqrt{5^{2}-4(3)(-7)}} {2(3)}[/tex]
[tex]x=\frac{-5(+/-)\sqrt{109}} {6}[/tex]
[tex]x=\frac{-5+\sqrt{109}} {6}[/tex]
[tex]x=\frac{-5-\sqrt{109}} {6}[/tex]
step 2
Let
[tex]\alpha=\frac{-5+\sqrt{109}} {6}[/tex]
[tex]\beta=\frac{-5-\sqrt{109}} {6}[/tex]
we need to calculate
[tex]\frac{1}{(3\alpha+5)^{2}}+ \frac{1}{(3\beta+5)^{2}}[/tex]
step 3
Calculate [tex](3\alpha+5)^{2}[/tex]
[tex](3\alpha+5)^{2}=[3(\frac{-5+\sqrt{109}} {6})+5]^{2}[/tex]
[tex]=[(\frac{-5+\sqrt{109}} {2})+5]^{2}[/tex]
[tex]=[(\frac{-5+\sqrt{109}+10} {2})]^{2}[/tex]
[tex]=[(\frac{5+\sqrt{109}} {2})]^{2}[/tex]
[tex]=[(\frac{25+10\sqrt{109}+109} {4})][/tex]
[tex]=[(\frac{134+10\sqrt{109}} {4})][/tex]
[tex]=[(\frac{67+5\sqrt{109}} {2})][/tex]
step 4
Calculate [tex](3\beta+5)^{2}[/tex]
[tex](3\beta+5)^{2}=[3(\frac{-5-\sqrt{109}} {6})+5]^{2}[/tex]
[tex]=[(\frac{-5-\sqrt{109}} {2})+5]^{2}[/tex]
[tex]=[(\frac{-5-\sqrt{109}+10} {2})]^{2}[/tex]
[tex]=[(\frac{5-\sqrt{109}} {2})]^{2}[/tex]
[tex]=[(\frac{25-10\sqrt{109}+109} {4})][/tex]
[tex]=[(\frac{134-10\sqrt{109}} {4})][/tex]
[tex]=[(\frac{67-5\sqrt{109}} {2})][/tex]
step 5
substitute
[tex]\frac{1}{(3\alpha+5)^{2}}+ \frac{1}{(3\beta+5)^{2}}[/tex]
[tex]\frac{1}{[(\frac{67+5\sqrt{109}} {2})]}+ \frac{1}{[(\frac{67-5\sqrt{109}} {2})]}[/tex]
[tex]\frac{2}{67+5\sqrt{109}} +\frac{2}{67-5\sqrt{109}}\\ \\\frac{2(67-5\sqrt{109})+2(67+5\sqrt{109})}{(67+5\sqrt{109})(67-5\sqrt{109})} \\ \\\frac{268}{1764}[/tex]
Simplify
Divide by 4 both numerator and denominator
[tex]\frac{268}{1764}=\frac{67}{441}[/tex]
Answer:
3) 67/441
Step-by-step explanation:
Comparing the given equation to the expressions you need to evaluate, you find there might be a simplification.
3x² +5x -7 = 0 . . . . . given equation
3x² +5x = 7 . . . . . . . add 7
x(3x +5) = 7 . . . . . . . factor
3x +5 = 7/x . . . . . . . . divide by x
Now, we can substitute into the expression you are evaluating to get ...
1/(3α +5)² +1/(3β +5)² = 1/(7/α)² +1/(7/β)² = (α² +β²)/49
__
We know that when we divide the original quadratic by 3, we get
x² +(5/3)x -7/3 = 0
and that (α+β) = -5/3, the opposite of the x coefficient, and that α·β = -7/3, the constant term. The sum of squares is ...
α² +β² = (α+β)² -2αβ = (-5/3)² -2(-7/3) = 25/9 +14/3 = 67/9
Then the value of the desired expression is ...
(67/9)/49 = 67/441
HELP ME WITH THIS QUESTION THANKS!✔✔
Answer:
-1 9/18 and then -32/40 and then 1 8/20
Step-by-step explanation:
The largest negatives is the least , then the second to least and then non-negative should be the greatest or the last
PLEASE HELP!!!!!!!!!!!!
How does the graph of g(x) = −(x + 3)^4 compare to the parent function of f(x) = x^4
A) g(x) is shifted 3 units to the right and 1 unit up
B) g(x) is shifted 3 units to the right and 1 unit down
C) g(x) is shifted 3 units to the right and reflected over the x-axis
D)g(x) is shifted 3 units to the left and reflected over the x-axis
I would rlly appreciate it!!! :)
Answer: Option D
Step-by-step explanation:
If we have a main function [tex]f (x) = x ^ 4[/tex]
And we perform the transformation:
[tex]g (x) = f (x + h) = (x + h) ^ 4[/tex]
Then it is fulfilled that:
If [tex]h> 0[/tex] the graph of [tex]f(x)[/tex] moves horizontally h units to the left
If [tex]h <0[/tex] the graph of [tex]f(x)[/tex] moves horizontally h units to the right
If we have a main function [tex]f (x) = x ^ 4[/tex]
And we perform the transformation:
[tex]g (x) = -f(x) = -x ^ 4[/tex]
Then it is fulfilled that:
The graph of [tex]g(x)[/tex] is equal to the graph of [tex]f(x)[/tex] reflected on the x axis
In this case we have to:
[tex]g(x) = -(x + 3)^4[/tex] and [tex]f(x) = x^4[/tex]
Therefore [tex]h=3>0[/tex] and [tex]g(x) = -f(x)[/tex]
This mean that: g(x) is shifted 3 units to the left and reflected over the x-axis.
How do u factor this?
Answer:(a+b)^2+(ab+a+b)2
Step-by-step explanation:
You break it up into two part, based on the exponents.
(a^2+b^2)+(2ab+2a+2b)
Now you can factor out from each...
(a+b)^2+(ab+a+b)2
Answer: (x+y+2)(x+y)
Step-by-step explanation:
Using square roots and factorising
3) Find the length of a rectangular lot with a perimeter of 92 m if the length is 8 m more than
the width.
Answer:
26 m
Step-by-step explanation:
Perimeter = 92 m
Length = 8 m more than width
Width: 20 m
Therefore,
length=26 mThe width of the rectangular lot is 19 m and the length is 27 m.
Explanation:The subject of this question is the calculation of the length of a rectangular lot. The perimeter of a rectangle is the sum of all its sides, given by the formula 2*(length + width). From the question, we know that the perimeter is 92 m, and the length is 8 m more than the width. Suppose 'w' is the width. Thus the length is 'w + 8' m.
So, we can set up the equation 2*(w + w + 8) = 92. Solving this equation will give us the value for the width (w) and consequently, the length by adding 8 to it.
Step-by-step solution:Combine like terms on the left side to get 2*(2w + 8) = 92.Then, distribute 2 to get 4w + 16 = 92.Subtract 16 from both sides to have 4w = 76.Finally, divide by 4 to find w = 19 m.The length (w+8) will then be 19m + 8m = 27m.Learn more about Rectangular Lot Dimensions here:https://brainly.com/question/34270507
#SPJ2
Identify an equation in point-slope form for the line parallel to y = x-7 that
passes through (-3,-2).
Answer:
B. y + 2 = ½(x + 3)
Step-by-step explanation:
Insert the coordinates into the formula with their CORRECT signs. Remember, in the Point-Slope Formula [y - y₁ = m(x - x₁)], all the negative symbols give the OPPOSITE terms of what they really are, which is the reason why you see two "+" in the equation. The ordered pair of [-3, -2] has two negative numbers, therefore you need to make them both positive in the equation [see above answer].
I am joyous to assist you anytime.
If you can draw one straight line through a polygon and cross more than two sides, the polygon is _______________.
A. concave
B. convex
C. regular
D. equiangular
Answer:
If you can draw one straight line through a polygon and cross more than two sides, the polygon is concave - A.
When you multiply a function by -1, what is the effect on its graph?
Step-by-step explanation:
[tex]\dfrac{a}{b}\cdot(-1)=-\dfrac{a}{b}[/tex]
On the number line, fractions a/b and -a/b lie on the opposite sides of the number 0, at the same distance (look at the picture).
PLEASE HELP! I have three questions:
1. 4 students from a class of 15 are going to be chosen to be on the dance committee. Find the number of different 4-person committees that can be made.
2. Leslie has 7 books. There is enough space on a shelf for 3 books. In how many ways can 3 of the 7 books be arranged on the shelf? (For this one I keep getting the answer 35, but its coming up wrong on my assignment.)
3. Out of the 12 girls who tried out for the softball team, 10 will be chosen for the team. Find the number of different 10-person teams.
Thank you!!
Answer: 1. 3 can be made 2. i believe it is only one way to put three books on a shelf 3. 3 i believe, its been awhile since i studied this
Step-by-step explanation:
In 46 years Christopher will be three times as old as he is right now. How old is he right now
Answer:
23
Step-by-step explanation:
Let his current age = x
Now if you add 46 to that, you will get x + 46.
x + 46
At which point he will be 3 times as old as he is now
x + 46 = 3x Subtract x from both sides.
x-x + 46 = 3x-x Combine
46 = 2x Divide by 2
46/2=2x/2 Do the division
23 = x
He is 23 right now
===============
It might be a little easier to see if you represent the situation a little more literally.
3x - 46 = x The answer comes to the same thing. You might think about which way you want to do it.
If you answer yo get 20 points
When the square of a number is increased by one, the result is four times the original
number. Find the number.
Answer:
n = 2 + 2√3 and n = 2 - 2√3
Step-by-step explanation:
Let the number be n.
Then n² + 1 = 4n.
Rearranging this in proper quadratic format:
n² - 4n + 1
Here the coefficients are a = 1, b = -4 and c = 1.
Then the discriminant is b²-4ac, or (-4)²-4(1)(1) ), or 16 - 4, or 12.
By applying the quadratic formula, we find that the roots are:
- (-4) ± √12
n = ------------------
2
or n = 2 + 2√3 and n = 2 - 2√3
Answer:
3.732 or 0.268 to the nearest thousandth.
Exact values are 2 + √12/2 or 2 - √12/2.
Step-by-step explanation:
Let the original number be x, then:
x^2 + 1 = 4x
x^2 - 4x + 1 = 0
x = [-(-4) +/- sqrt(16 - 4*1*1]) / 2
x = (4 + sqrt12)/ 2 , (4 - sqrt12) / 2
= 3.732, 0.268.
wht equation describes a parabola that opens up or down and whos vertex is at the point (h,v)
Answer:
[tex]f(x)=a(x-h)^2+k[/tex]
Vertex form.
Step-by-step explanation:
You are talking about the vertex form for a parabola.
[tex]f(x)=a(x-h)^2+k[/tex] tells us:
A) The vertex is (h,k).
B) Open up (if a is positive) or open down (if a is negative)
C) a also tells us how much it is vertically stretched or compressed.
raph the equation with a diameter that has endpoints at (-3, 4) and (5, -2). Label the center and at least four points on the circle. Write the equation of the circle.
Answer:
Equation:
[tex]{x}^{2} + {y}^{2} + 2x - 2y - 35= 0[/tex]
The point (0,-5), (0,7), (5,0) and (-7,0)also lie on this circle.
Step-by-step explanation:
We want to find the equation of a circle with a diamterhat hs endpoints at (-3, 4) and (5, -2).
The center of this circle is the midpoint of (-3, 4) and (5, -2).
We use the midpoint formula:
[tex]( \frac{x_1+x_2}{2}, \frac{y_1+y_2,}{2} )[/tex]
Plug in the points to get:
[tex]( \frac{ - 3+5}{2}, \frac{ - 2+4}{2} )[/tex]
[tex]( \frac{ -2}{2}, \frac{ 2}{2} )[/tex]
[tex]( - 1, 1)[/tex]
We find the radius of the circle using the center (-1,1) and the point (5,-2) on the circle using the distance formula:
[tex]r = \sqrt{ {(x_2-x_1)}^{2} + {(y_2-y_1)}^{2} } [/tex]
[tex]r = \sqrt{ {(5 - - 1)}^{2} + {( - 2- - 1)}^{2} } [/tex]
[tex]r = \sqrt{ {(6)}^{2} + {( - 1)}^{2} } [/tex]
[tex]r = \sqrt{ 36+ 1 } = \sqrt{37} [/tex]
The equation of the circle is given by:
[tex](x-h)^2 + (y-k)^2 = {r}^{2} [/tex]
Where (h,k)=(-1,1) and r=√37 is the radius
We plug in the values to get:
[tex](x- - 1)^2 + (y-1)^2 = {( \sqrt{37}) }^{2} [/tex]
[tex](x + 1)^2 + (y - 1)^2 = 37[/tex]
We expand to get:
[tex] {x}^{2} + 2x + 1 + {y}^{2} - 2y + 1 = 37[/tex]
[tex]{x}^{2} + {y}^{2} + 2x - 2y +2 - 37= 0[/tex]
[tex]{x}^{2} + {y}^{2} + 2x - 2y - 35= 0[/tex]
We want to find at least four points on this circle.
We can choose any point for x and solve for y or vice-versa
When y=0,
[tex]{x}^{2} + {0}^{2} + 2x - 2(0) - 35= 0[/tex]
[tex]{x}^{2} +2x - 35= 0[/tex]
[tex](x - 5)(x + 7) = 0[/tex]
[tex]x = 5 \: or \: x = - 7[/tex]
The point (5,0) and (-7,0) lies on the circle.
When x=0
[tex]{0}^{2} + {y}^{2} + 2(0) - 2y - 35= 0[/tex]
[tex] {y}^{2} - 2y - 35= 0[/tex]
[tex](y - 7)(y + 5) = 0[/tex]
[tex]y = 7 \: or \: y = - 5[/tex]
The point (0,-5) and (0,7) lie on this circle.
Type the correct answer in the box. For this item, any non-integer answer should be entered as a decimal rounded to the hundredths place. Statistics show that a certain soccer player has a 63% chance of missing the goal each time he shoots. If this player shoots twice, the probability that he scores a goal both times is_____ %.
Answer:
13.69%.
Step-by-step explanation:
The probability he scores in 1 shot = 1 - 0.63 = 0.37.
The probability that he scores twice in 2 shots = 0.37 * 0.37
= 0.1369
= 13.69%.
The probabilities are multiplied because the 2 events are independent.
Answer:
For plato user the answer is 13.69 %.
Step-by-step explanation:
If this player shoots twice, the probability that he scores a goal both times is
13.69 %.
Solve the equation 25x^2+121=0
Subtract 121 from both sides:
[tex]25x^2=-121[/tex]
Divide both sides by 25:
[tex]x^2 = -\dfrac{121}{25}[/tex]
The solutions would be
[tex]x = \pm\sqrt{-\dfrac{121}{25}}[/tex]
This expression cannot be evaluated using real numbers, because the square root of negative numbers are not allowed. If we're using complex numbers, the solutions are
[tex]x = \pm\sqrt{-\dfrac{121}{25}} = \pm\dfrac{11i}{5}[/tex]
The equation y=mx+b is the slope-intercept form of a linear equation.
Solve y=mx+b for m
Answer:
[tex]\large\boxed{m=\dfrac{y-b}{x}}[/tex]
Step-by-step explanation:
[tex]y=mx+b\to mx+b=y\qquad\text{subtract}\ b\ \text{from both sides}\\\\mx+b-b=y-b\\\\mx=y-b\qquad\text{divide both sides by}\ x\neq0\\\\\dfrac{mx}{x}=\dfrac{y-b}{x}\\\\m=\dfrac{y-b}{x}[/tex]
Answer: [tex]m=\frac{y-b}{x}[/tex]
Step-by-step explanation:
The equation of the line in Slope-Intercept form is:
[tex]y=mx+b[/tex]
Where "m" is the slope of the line and "b" is the y-intercept.
Then, to solve for the slope "m", you can follow these steps:
- You need to subtract "b" from both sides of the equation:
[tex]y-b=mx+b-b\\\\y-b=mx[/tex]
- Finally, you can divide both sides of the equation by "x". Then:
[tex]\frac{y-b}{x}=\frac{mx}{x}\\\\m=\frac{y-b}{x}[/tex]
Identify the explicit function for the sequence in the table.
1 9
2 14
3 19
4 24
5 29
,
O A. a[n) = 9+ (n - 1)•5
O B. a(n) = 5 + (n - 1)•9
O.C. a[n) = 9 (n-1)
O D. a(n) = 5(n-1)
Answer:
A.
[tex]a_n=9+(n-1)\cdot 5[/tex].
Step-by-step explanation:
The common difference is 5. The y values are going up by 5. So this is an arithmetic sequence since we have a common difference.
The explicit form for arithmetic sequence is:
[tex]a_n=a_1+(n-1) \cdot d[/tex] where d represents the commom difference and [tex]a_1[/tex] is the first term.
Here the first term is [tex]a_1=9[/tex] and we already determined the value for d which is 5.
Inputing these values for first term and common difference give:
[tex]a_n=9+(n-1)\cdot 5[/tex].
Answer:
the answer is A
Step-by-step explanation:
EXPLAIN!!!!!!!!!!!!!!
Answer:
111
Step-by-step explanation:
because the lines are parallel and they are on opposite sides its like having two angles on the same line but on different sides so they are supplementary meaning they add up to 180 and 180-69 = 111
please mark brainliest :)
What is the complete factorization of the polynomial below x^3+5x^2-x-5
Answer:
(x+5)(x-1)(x+1)
Step-by-step explanation:
Let's attempt factoring by grouping:
So what this means we first want to group the first two terms together and second two terms together, like so:
(x^3+5x^2)+(-x-5)
Now we factor what we can from each pair:
x^2(x+5)+1(-x-5)
Notice x+5 doesn't appear to be the same as -x-5 so we should factor out -1 instead of 1 in the second pair of terms:
x^2(x+5)-1(x+5)
You have two terms: x^2(x+5) and -1(x+5); they have a common factor of (x+5) so we can factor it out:
(x+5)(x^2-1)
You can actually factor this more because x^2-1 is a difference of squares.
The formula for factoring a difference of squares is u^2-v^2=(u-v)(u+v).
So the factored form of x^2-1 is (x-1)(x+1).
So the complete factored form of our expression we had initially is
(x+5)(x-1)(x+1).
Answer:
[tex]\large\boxed{x^3+5x^2-x-5=(x+5)(x-1)(x+1)}[/tex]
Step-by-step explanation:
[tex]x^3+5x^2-x-5\qquad\text{distributive}\\\\=x^2(x+5)-1(x+5)\\\\=(x+5)(x^2-1)\\\\=(x+5)(x^2-1^2)\qquad\text{use}\ a^2-b^2=(a-b)(a+b)\\\\=(x+5)(x-1)(x+1)[/tex]
PLEASE HELP PLEASE
Which number is not divisible by either of the numbers 3 and 5?
A. 5000
B. 2374
C. 1203
D. 2505
Answer:
The answer is B. 2374
Answer:
B. 2374
Step-by-step explanation:
Division by 5: If a number ends in 0 or 5 it is divisible by 5.
A. 5000 is divisible by 5.
D. 2505 is divisible by 5.
Division by 3: If the sum of the digits of a number is divisible by 3, then the number is divisible by 3.
B. 2374
Add the digits of 2374: 2 + 3 + 7 + 4 = 16. 16 is not divisible by 3, so 2374 is not divisible by 3. It is also not divisible by 5 since it does not end in 0 or 5.
C. 1203
Add the digits of 1203: 1 + 2 + 0 + 3 = 6. Since 6 is divisible by 3, 1203 is divisible by 3.
Answer: B. 2374
Decide which part of the quadratic formula tells you whether the quadratic equation can be solved by factoring.
−b b2 − 4ac 2a
Use the part of the quadratic formula that you chose above and find its value, given the following quadratic equation:
4x2 + 6x + 2 = 0
Answer:
b^2-4ac, the value of the discriminant is 4
Step-by-step explanation:
The part b^2-4ac called the discriminant will tell you how many solutions a particular equation has, after plugging in the values you can tell how many solutions and what type of solutions that equation has by looking at whether the result is positive and a perfect square, positive, zero, or negative. If the result is a positive perfect square, there will be two rational solutions; if the result is positive there will be two real zeros; if the result is zero, there is one real zero; if the result is negative, there will be two complex conjugates or imaginary terms.
To find the value of the discriminant plug in the values of the equation.
6^2-4(4)(2)=4
The value of the discriminant in this particular equation is a perfect square, that means that there are two rational solutions. Put simply, this equation is factorable.
4x^2 + 6x + 2 = 0
(x+1)(4x+2)=0
x=-1 or -1/2
Answer:
The above explanation was correct.
To make it clear, just type 4 as the answer
What is the square root of -1?
Т -
ОООО
Т -
Answer:
i
Step-by-step explanation:
The square root of -1 is i which is an imaginary number
Which statement is true about lines a and b?
They are parallel lines.
They are perpendicular lines.
They are skew lines.
They will intersect.
It would be C. they are skew on ED :)
Answer: C
Step-by-step explanation: your welcome
There are 22 participants in a spelling bee. In how many ways can the top 5 participants finish? Use the formula for permutations to find your answer
Answer:
3,160,080Explanation:
The formula for permuations is nPk:
[tex]_nP_k=\frac{n!}{(n-k)!}=(n)(n-1)(n-2)...(n-k+1)[/tex]Where n is the total number of elements from which you must choose combinations of k number of elements, and where the order of selection is relevant.
In this case n = 22 (the number of participants), k = 5 (the number of top participants). Since, the order in which the participants finish is relevant, then you have to use the formula of permutations, such as the question states.
Calculations:
[tex]_{22}P_5=\frac{22!}{(22-5)!}=22.21.20.19.18=3,160,080[/tex]4,792÷8 show your work
Answer:
4,792 ÷ 8 = 599Step-by-step explanation:
Look at the picture.
Use the long division.
Solve for x.
A. 2
B. 4
C. 6
D. 8
The full length of one line times the length of the line outside the circle is equal the the other line.
(x-1) +5 x 5 = (2+x)+4 x 4
Simplify:
(x+4) x 5 = (x +6) x 4
5x +20 = 4x +24
Subtract 20 from each side:
5x = 4x +4
Subtract 4x from each side:
x = 4
The answer is B. 4
PLEASE ANSWER 9 and 10
GEOMETRY SOLVING FOR MISSING ANGLE
Answer:
9. 75°
10. 60°
Step-by-step explanation:
Note the angle-intercept theorem. If you create an angle in the opposite side of a circle from 2 points on other side, the arc will have a measure TWICE that of the intercepted angle created on other side.
Question 9
Arc WX has a measure 76, thus the angle created is Angle V, which should be HALF of that. So angle V is 76/2 = 38
Now looking at the triangle inside the circle, we know three angles of a triangle add up to 180, thus we can write and solve for "?" angle:
X + W + V = 180
? + 67 + 38 = 180
? + 105 = 180
? = 180 - 105 = 75°
Question 10
Using the theorem we can say that Angle B is HALF of ARC XYZ.
So,
2*Angle B = Arc XY + Arc YZ
2*102 = Arc XY + 124
204 = Arc XY + 124
Arc XY = 204 - 124 = 80°
Also, Arc BX + Arc XY is twice that of Angle Z (which is 70), thus
Arc BX + Arc XY = 70 *2
Arc BX + Arc XY = 140
Arc BX + 80 = 140
Arc BX = 140 - 80 = 60°
Determine the area and perimeter of figure described:
square with sides of length 9mm
Answer:
Perimeter= 36mm
Area= 81mm
Step-by-step explanation:
WILL GIVE BRAINLEST SUPER EASY A coyote can run up to 43 miles per hour while a rabbit can run up to 35 per hour. Write two equivalent expressions and then find how many more miles a coyote can run in six hours than a rabbit at these rates.
48 more miles
Coyote= 43h
Rabbit= 35h
Coyote= 43(6)= 258
Rabbit= 35(6)= 210
Now subtract 258 by 210
258-210= 48